POLYSEMY AND MEANING EXTENSION OF JAVANESE BODY-PART TERMS: COGNITIVE SEMANTIC STUDY - Muhammad Walimsyah Sitorus; Murniati Br Barus; Nanda Dwi Astri; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2026)
Body-part terms are a productive source of lexical meaning extension, but Javanese research has mainly described selected metaphors and proverbs rather than the distribution of related senses in a general corpus. Purpose: This study identifies the body-part lexemes attested in a contemporary Javanese treebank, distinguishes literal and extended uses, and reconstructs the cognitive mechanisms linking their senses. Method: A corpus-assisted qualitative analysis was conducted on the UD Javanese-CSUI treebank containing 1,000 sentences and 14,343 tokens. Thirty-one candidate body-part forms were searched, normalized into lexical families, and examined through concordance-based contextual analysis. Metaphorical extension was diagnosed through perceived similarity, while metonymic extension was identified through contiguity, function, or part-participant association. Results: Fifty-seven raw tokens were retrieved; one proper name was excluded, leaving 56 relevant tokens in 12 lexical families. Extended uses accounted for 29 tokens (51.8%). The domain ATI/MANAH dominated the extended data and lexicalized emotion, moral disposition, inner voice, and psychological stability. TANGAN/ASTA encoded control and responsibility, while SIKIL, KUPING, LENGEN, and JANTUNG produced participant, evaluative, object-part, and emotional extensions. Conclusion: Javanese body-part polysemy is systematic but distributionally unequal. Internal-state meanings are highly conventionalized, whereas object and participant extensions are sparse in the sampled corpus. The findings support a usage-based semantic-network model and provide a replicable basis for Javanese lexicography and figurative-language annotation.